A polygonal-FEM technique in modeling large sliding contact on non-conformal meshes. Issue 5 (6th July 2015) - Khoei, Amir R.; Yasbolaghi, R.; Biabanaki, S.O.R.
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – In this paper, the polygonal-FEM technique is presented in modeling large deformation – large sliding contact on non-conformal meshes. The purpose of this paper is to present a new technique in modeling arbitrary interfaces and discontinuities for non-linear contact problems by capturing discontinuous deformations in elements cut by the contact surface in uniform non-conformal meshes. Design/methodology/approach – The geometry of contact surface is used to produce various polygonal elements at the intersection of the interface with the regular FE mesh, in which the extra degrees-of-freedom are defined along the interface. The contact constraints are imposed between polygonal elements produced along the contact surface through the node-to-surface contact algorithm. Findings – Numerical convergence analysis is carried out to study the convergence rate for various polygonal interpolation functions, including the Wachspress interpolation functions, the metric shape functions, the natural neighbor-based shape functions, and the mean value shape functions. Finally, numerical examples are solved to demonstrate the efficiency of proposed technique in modeling contact problems in large deformations. Originality/value – A new technique is presented based on the polygonal-FEM technique in modeling arbitrary interfaces and discontinuities for non-linear contact problems by capturing discontinuous deformations in elements cut by the contact surface in uniform non-conformal meshes.